Enjeu de la subjectivité et nouvelles approches de la stylistique française - Villanueva, María Luisa (Caplletra. Revista Internacional de Filologia, 2000)
Our aim in this article is to outline the evolution of stylistics in France trying to build up some conceptual criteria that allow us to explain present tendencies concerning such notions as intersubjectivity and semiosphere, as well as the description of a number of rhetoric phenomena behaving as a sort of crossroads where rhetoric, pragmatics and semantics come together. Finally, we argue that not only interpretation is a game of multiple structures and perspectives, but also that style in text may similarly result from the diversity of languages and from the challenge some represent of discourse boundaries.